The Analysis of Teacher Policy in Indonesia - Soni Ariawan (Universitas Islam Sultan Agung, 2022)
The present qualitative research aims to investigate teacher policy in Indonesia viewed from international teacher standard revealed in the Teacher Policy Development Guide of United Nation. There are four dimensions as the focus of analysis: underpinning values, the purpose, key principles of implementation and key dimension for comprehensive teacher policy. Content analysis was employed to gauge the data from the rule of law on teacher and lecturer in Indonesia number 14 year 2005 about teacher and lecturer that is more specifically broken down into policy number 74 year 2008 about teacher. In addition, the researcher carefully investigated four dimensions revealed in the Indonesian teacher policy document as well as highlighted the results in the form of table. The findings confirmed that Indonesia has a comprehensive policy dealing with education system and teacher which reflects several international standards and features as well as accommodates local values. On the other hand, teacher policy in Indonesia is still presented in general language instruction without a specific implementation guide. To conclude, both policies have different languages and terminology in some extend but it has the same basic idea in terms of human right and democratic values both in the context of teacher policy and education in general.Â